2016
DOI: 10.1016/j.applthermaleng.2015.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of the hot blast furnace slag on coal gasification reaction

Abstract: The main objective of this research was to comprehensively investigate the role of the hot blast furnace slag (BFS) played in coal gasification reaction process so as to improve the utilization of BFS waste heat and enhance H 2 and CO content in the syngas. The BFS characterizations, such as the heat carrier, catalyst, reactant, and the sulfide capacity were investigated. The results indicated that about 61% BFS waste heat could be recovered by coal gasification, and the exergy loss (EXL) of which was only 409… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 45 publications
2
10
1
Order By: Relevance
“…In addition, an increase in temperature was found to also increase the carbon conversion process slightly. with those reported in the literature for other gasification process [63][64][65][66][67] at the same temperature. As can be seen, the obtained results agree with previously reported data to within an absolute average difference of 6.5%.…”
Section: 5influence Of Partial Pressure Of Oxygen On Syngas Qualitysupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, an increase in temperature was found to also increase the carbon conversion process slightly. with those reported in the literature for other gasification process [63][64][65][66][67] at the same temperature. As can be seen, the obtained results agree with previously reported data to within an absolute average difference of 6.5%.…”
Section: 5influence Of Partial Pressure Of Oxygen On Syngas Qualitysupporting
confidence: 84%
“…The comparison was performed at temperatures ranging from 1000°C and 1300°C to show that the fuel conversion for the gasification with molten metal oxides is effectively the same as those reported for other gasification processes and techniques. For example, the difference between the present and previous results are 3.1%, 5.1%, 6.5% and 2.6% for Siriwardane et al [65], Dennis et al [67], Li et al [63] and Yu et al [64], respectively. Figure 15 presents the dependence of fraction of exergy in the syngas product and the hot vitiated air on the circulation ratio.…”
Section: 5influence Of Partial Pressure Of Oxygen On Syngas Qualitycontrasting
confidence: 81%
“…Slag is applied in specialized market sectors. According to the European association of manufacturing and utilization of ferrous slag products (EUROSLAG), industrial slags found their predominant application in different fields such as road construction [6][7][8], cement production [9][10][11][12] and can be also used as heat carriers [13].…”
Section: Introductionmentioning
confidence: 99%
“…(8) and Eq. (9). Overall, the reaction rate equation (including E a and k 0 ) of steam gasification with BFS as heat carrier was established, as shown in Table 5.…”
Section: Kinetic Mechanism Of Steam Gasificationmentioning
confidence: 99%
“…In face of this challenge, Liu [4] proposed the theory of coal gasification reaction with molten BFS as heat carrier to produce hydrogen-rich syngas. Based on this theory, an attempt was made by Duan [5][6][7][8][9][10] to explore the potential of hydrogen-rich syngas production and waste heat recovery of slag. Li and Yu et al [11][12][13][14][15] also carried on the thorough research in the aspect of gasification and waste heat recovery.…”
Section: Introductionmentioning
confidence: 99%